Sustainable watercolor: representative images of the conception of sustainability based on drawings by children and adolescents from João Pessoa - Coelho, Ana Lúcia de Araújo Lima; Santos, Helaine Cristine Carneiro dos; Silva, Arthur William Pereira da; Coelho, Christiano; Oliveira, Brenda Nathália Fernandes (Revista de Administração da UFSM, 2018)
Beginning with the fact that today's children and adolescents will be the managers of future societies, for the viability of any form of future sustainability, it is important to understand how these individuals imagine managing available resources to subsequently enable the alignment of these ways to conceive with the principles of this new way of managing through education for sustainability. Thus, the objective of this study was to analyze notions of sustainability based on the drawings of elementary and middle students from a private school located in the city of João Pessoa, Paraíba. The results showed that the conception of most elementary students is focused primarily on the environmental pillar and, to a lesser extent, on the social pillar, whereas middle school students tackle broader conceptions in their drawings involving environmental, social, and economic elements. These results serve as preliminary evidence of the effectiveness of educational actions for sustainability in the school investigated. However, they do not prove it, thus allowing for more in-depth investigation.